MANAJEMEN PENGANGKUTAN SAMPAH DI KOTA AMLAPURA - Nadiasa, Mayun; Sudarsana, Dewa Ketut; Yasmara, I Nyoman (Jurnal Ilmiah Teknik Sipil; Vol. 13, No. 2 Juli 2009, 2009)
Base on the existing conditions, garbage transportation in Amlapura still faces problems. Garbage transportation in rush hour causes traffic jam. The existing temporary garbage place (TPS) has not been designed and equipped with devices that can separate organic and unorganic garbage, thus it is still mixed up in one container. This condition needs a deeper attention in order to improve the existing garbage transportation management. This research aims to improve the weakness of the current garbage transportation system. The SNI No. 19-2454-2002 was used as an approached method to solve this problem. In order to determine appropriate tariffs that can cover the operational cost of garbage transportation, the method of financial assessment was used namely Net Present value (NPV), Benefit Cost Ratio (BCR), and Internal Rate of Return (IRR). The garbage transportation system chosen for a compactor truck was fixed container transportation mode and for an arm roll truck was empty container tranportation mode. The number of vehicle required to carry out garbage transportation in Amlapura was 4 compactor trucks for organic garbages, 3 compactor trucks for unorganic garbages, and a unit of arm roll truck for organic and inorganic garbages. The reguired time for picking garbage was about six hours per day. The numbers of TPS needed in Amlapura were 213 bin containers with capacity of 0.36 m3 for organic TPS and 137 units for the unorganic. It was also required 5 units of organic TPS and 3 units of the unorganic that using containers with capacity of 4 m3. It was assumed that this investment would be financed by 100% of bank loan. The result of this study shows that this investment will be reliable if the applied tarrif is Rp.15.000/family/month for household, Rp.25.000/room/month for hotel, Rp.5000/seat/month for restaurant, Rp.30.000/unit/month for shop, Rp.20.000/unit/month for school and office, Rp. 30.000/seller/month for market trader, Rp. 30.000/month for small scale industry and Rp. 40.000/month for middle scale industry.
Keywords: Garbage Transportation Design System, Organization, Investment, Retribution